A REVIEW : CD FABRICATION WITH TECHNOLOGY DIFFERENT FROM CONVENTIONAL METHOD - B, Harini; Kommi, Venkatesh; Sashank, Keerthi; Roy, Anitha (International Journal of Psychosocial Rehabilitation, 2020)
The difference in Complete denture fabrication with technology and conventional methods and its evolution over the past few years. Both conventional and newer technology have their own advantages and disadvantages in fabricating complete dentures. The conventional method of fabricating was the oldest and earliest method used for fabrication. Now this method of fabrication of complete dentures has been slowly replaced by technology. Technology involves (CAD/CAM) Computer - aided design / computer - aided manufacture of complete dentures in dentistry. Time management is very less in opting digital denture methods over conventional method as it reduces the time for recording from the patient’s, processing time in the labs and also the trial method in checking the final dentures on the patients .Clinical sitting also plays a major rule in digital denture and conventional method by limiting the number of visits to the dentist and mainly the maintenance of complete dentures differ both in CAD/ CAM and conventional method of fabrication. Many countries are eventually adapting CAD CAM procedures as the technology is available widely around the world. In this review, an overview of complete denture fabrication with technology different from conventional method, necessities in opting technology over conventional method and the advantages and disadvantages of digital dentures and conventional method are reviewed. Overall, the need for changing from conventional method to digital technology for fabricating complete dentures.